Legal Aspects of Governance Regarding Single Candidates Against Empty Boxes in Regional Elections and Their Implications for Indonesian Democracy - Janah, Eka Nur; Jaya Wardana, Dodi (Jurnal Daulat Hukum, 2025)
Regional elections with a single candidate against an empty ticket raise fundamental questions regarding their compliance with democratic principles and constitutionality, as well as their impact on political stability. This study aims to analyze the legal aspects of governance related to this mechanism and its impact on Indonesia's democratic system. The method used is normative juridical with a statutory and conceptual approach. Data were obtained through a literature review of relevant laws and doctrines. Legitimately legitimized by Constitutional Court Decision No. 100/PUU-XIII/2015, this mechanism formally addresses questions of constitutionality by guaranteeing citizens' voting rights and the continuity of government. While providing space for voter participation, this mechanism has the potential to limit the public's right to choose from a variety of options, which is the essence of democracy. Constitutionally, its existence is questionable because it limits fair play in elections. However, substantively, this practice sparks debate about democratic principles because it drastically limits voter choice and reduces the quality of the contestation of ideas. Its impact on political stability is twofold: in the short term, it can maintain stability by preventing a power vacuum. However, in the long term, the victory of a single candidate with potentially low public legitimacy could erode trust, weaken checks and balances, and ultimately threaten healthy political stability. The Regional Election Law must be thoroughly revised to ensure a healthy and fair contestation.